Factors affecting knowledge sharing in a private higher education / Hafiza Adenan - Adenan, Hafiza (Institute of Graduate Studies, UiTM, 2018)
Currently, Malaysia shifts towards building a knowledge-based society; therefore, higher education institutions (HEIs) particularly private HEIs now face ever growing demands for sharing quality resources and expertise. Consequently, knowledge sharing in academia has become a rising concern. As known, knowledge sharing among academic staffs would enhance the capability and quality of teaching and research undertaken by the private HEIs. Hence, the private HEIs should implement various efforts to develop more effective knowledge sharing among academic staffs. Therefore, the purpose of this study is to identify and investigate how and why the individual, organizational and technological factors can hinder or stimulate knowledge sharing among academic staffs at a private HEI. The qualitative methodology that is multiple case studies were applied to achieve the study's purpose. In-depth interview, focus group interview and document analysis formed the data collection method for this study. The in-depth interviews were done with four academic staffs of a private HEI, while, the focus group consisted with five academic staffs as the respondents. The theory of Planned Behavior by Ajzen (1991) and Social Technical approach by Pan and Scarbrough (1998) were used to determine and explore the individual, organizational and technological factors that able to stimulate or inhibit Malaysian private academic staffs' knowledge sharing behavior…